1987
DOI: 10.1111/j.1438-8677.1987.tb02006.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Staminal Filament of Gasteria Verrucosa

Abstract: The development of the lower part of the stamen of Gasteria verrucosa (Mill.) H. Duval, the filament, was investigated using interference contrast, transmission and scanning electron microscopy, and was related to the development of the anther.The filament extends during its entire development, in the younger stages mainly in the basal region, in the older stages in the tip. Up to maturity the solidity is gradually improved by the progressive thickening of the tangential epidermal wall and the cuticle from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The stamen filament is known to be the organ by which the anther is supplied with nutrients during all pollen development (Keijzer, Hoek, and Willemse, 1987). Throughout the anther growth phase, we have shown that, despite a reduced growth, sucrose concentration in the filament is the highest of all the organs of the flower bud.…”
Section: Discussionmentioning
confidence: 61%
“…The stamen filament is known to be the organ by which the anther is supplied with nutrients during all pollen development (Keijzer, Hoek, and Willemse, 1987). Throughout the anther growth phase, we have shown that, despite a reduced growth, sucrose concentration in the filament is the highest of all the organs of the flower bud.…”
Section: Discussionmentioning
confidence: 61%
“…In a recent investigation of the filament development in Gasteria verrucosa (Mill.) H. Duval we found that the tracheary elements in the collapsing filament tip remain open during anther dehiseenee (Keijzer et al, 1987). It was suggested that the sudden decrease of starch at dehiseenee led to osmotic withdrawal of water from the anther into the filament, thus promoting anther dehydration and dehiseenee.…”
Section: Introductionmentioning
confidence: 90%
“…Observations on the behaviour of the filament and the connective tissue have only recently been included in accounts of anther development (Mepham & Lane, 1969;Pacini, 1986). Studies exclusively devoted to this topic are scarce (Schmid, 1976-Keijzer, Hoek & Willemse, 1987. Schmid (1976) discussed the relationships between filament characteristics and anther dehiseenee, but he did not specially focus on the filament tip.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last stage before dehiscence, the anthers also dehydrate and there is evidence that this causes the collapse of the cells in the vascular bundle in the tip of the filament (Keijzer et al 1987a(Keijzer et al , 1987b. We show that this did not occur in ethylene-insensitive anthers at stage 12, suggesting that these anthers are less dehydrated (Fig.…”
Section: Discussionmentioning
confidence: 60%